2006
DOI: 10.1176/ajp.2006.163.4.697
|View full text |Cite
|
Sign up to set email alerts
|

Body Image and Attitudes Toward Male Roles in Anabolic-Androgenic Steroid Users

Abstract: Both body-image pathology and narrow stereotypic views of masculinity appear to be prominent among men with long-term AAS use. Although our cross-sectional observations cannot confirm that these factors help to cause or perpetuate AAS use, a causal hypothesis is certainly plausible and deserving of further testing in longitudinal studies. If these factors are indeed causal, then AAS users might respond to cognitive behavior approaches that simultaneously take aim at both types of maladaptive beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
90
1
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(109 citation statements)
references
References 28 publications
6
90
1
10
Order By: Relevance
“…For instance, males who use AAS for performance-based motives may be less likely to respond to appearance-based prevention models (Stice et al, 2006), and may require a modified preventative approach. Previous findings have suggested that body image psychopathology in AAS users may be more apparent in long-term users, with brief, experimental users typically demonstrating little body image psychopathology (Kanayama et al, 2006). Interestingly, we noted no differences in the duration of AAS use as a function of motivation for use, suggesting that, when use is primarily for appearance-related reasons, both shorter-term and longer-term AAS users may be vulnerable to greater body image-related psychopathology.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…For instance, males who use AAS for performance-based motives may be less likely to respond to appearance-based prevention models (Stice et al, 2006), and may require a modified preventative approach. Previous findings have suggested that body image psychopathology in AAS users may be more apparent in long-term users, with brief, experimental users typically demonstrating little body image psychopathology (Kanayama et al, 2006). Interestingly, we noted no differences in the duration of AAS use as a function of motivation for use, suggesting that, when use is primarily for appearance-related reasons, both shorter-term and longer-term AAS users may be vulnerable to greater body image-related psychopathology.…”
Section: Discussioncontrasting
confidence: 52%
“…Negative body image is a primary risk factor for AAS use (Field et al, 2014;Van den Berg et al, 2007;Cafri et al, 2006;Kanayama et al, 2006;Riciardelli and McCabe, 2004). For example, Cafri et al (2006) found that a desire for increased muscularity was significantly associated with AAS use among young adult men.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of negative body image is a significant public health concern due to its negative physical and psychological health outcomes. People with negative body image are more likely to experience disordered eating (Stice, 2002), depression and suicidal ideation (Brausch & Gutierrez, 2009;Kanayama, Barry, Hudson, & Pope, 2006), and drug and alcohol misuse (Kanayama, et al, 2006;Nelson, Lust, & Story, 2009). Exposure to media images of idealised thin and muscular models is a significant risk factor for poor body image (Levine & Murnen, 2009;Slater & Tiggemann, 2006).…”
Section: Seeing the Beauty In Everyday People: A Qualitative Study Ofmentioning
confidence: 99%
“…Em relação ao uso de substâncias ergogênicas, apesar de o uso de esteróides anabolizantes e suplementos alimentares ser freqüentemen-te considerado como uma característica do portador da DISMUS (2,8,20) , na amostra 1, dados desta pesquisa não discriminaram os grupos B/P < 1 e B/P > 1 quanto à declaração espontânea de utilização dos esteróides. Por outro lado, o uso dos ditos suplementos alimentares foi reportado de forma significativamente mais freqüente no grupo B/P > 1.…”
Section: Discussionunclassified
“…O indivíduo portador de DISMUS apresenta distorção da auto-imagem corporal, percebendo seus músculos como muito pouco desenvolvidos, apesar da visível hipertrofia muscular (7) , e procura ativamente aumentar sua massa muscular, através de exercícios excessivos e do uso de substâncias ergogênicas (8) e de dietas hiperprotéicas (9) . Tal apresentação clínica foi descrita pela primeira vez sob o título de Dismorfia Muscular em 1997 por Pope et al (10) .…”
Section: Introductionunclassified